Language development in preschool children - Ainnun Ibrahim Hamid; Muhammad Razidinnor; Yuliana Selan (PROCEEDING UMSURABAYA, 2020)
Abstract. One area of development in the growth of basic skills in kindergarten is languagedevelopment. Language development is a person's ability to communicate with others. Language development in Preschool Children is a change in the sound-symbol system that affects the ability to speak. Early childhood can identify themselves and interact and work together with others. Language allows children to translate experiences into symbols that can be used to communicate and think. Language skills in kindergarten age children are divided into five aspects of development: phonetic, semantic, syntactic, morphemic, pragmatic. With language, children can communicate their intentions, goals, thoughts, and feelings to others. Kindergarten age children are school-aged children who are at a vulnerable age of 4-6 years, where during this time, the child develops very rapidly.Keywords: language development and Preschool children